PENGARUH TEKNIK ROOLING MASSAGE TERHADAP KELANCARAN PENGELUARAN ASI PADA IBU HAMIL TRIMESTER III - Tanjung, Wiwi Wardani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The Exclusive Breastfeeding has been shown to have an impact better on health growth, development, and all the impacts short and long term, but there are still many mothers who do not provide exclusive breastfeeding. One of the reasons mom does not provide exclusive breastfeeding to the baby was due to the release of breast milk that was not smooth that happened due to inhibition of the hormone prolactin which produces breast milk. Rolling Massase Technique was one action which gives a relaxing sensation to the mother and smooth the flow of nerves as well as the milk duct. The purpose of this research was to know the influence of rooling massage techniques on the smooth release of breast milk in third trimester pregnant women in the work area In Public Health Center Of Batunadua 2020. This type of research was quantitative research with a quasi experimental design used the Post Test Only Design with Control Group design. The population in this study are all trimester III pregnant women who came to the Public Health Center Of Batunadua as many as 32 people. The sample in this study was 16 people in the intervention group and 16 people in the control group by used accidental sampling method. The analysis used was the Wilcoxon test. The results showed that massage rooling technique effect on smoothness expressing breastmilk in pregnant women Trimester III with p value = 0.008 (p <0.05). It was hoped that the Public Health Center Of Batunadua In Padangsdimpuan to do health education or health promotion which can be given to pregnant women to prepare for smooth operation expressing breastmilk like perform rooling massage technique.